A Comparison of Single and Multi-Stream Recycling Systems in Ontario, Canada - Calvin Lakhan (Resources, 2015)
This study examines differences in cost and recycling performance between single and multi-stream recycling systems in Ontario, Canada. Using panel data from 223 provincial municipalities spanning a ten year period, focus is placed on analyzing: (a) Are material management costs for municipalities who implement single stream collection less than those that implement multi stream collection? (b) Are recycling rates for single stream municipalities higher than municipalities with multi stream collection? (c) Do municipalities with multi stream collection realize higher revenues from the sale of recyclable material? The results of the analysis show that while single stream recycling programs recycle more than multi stream programs, they face significantly higher material management costs. This was contrary to the prevailing opinion that single stream recycling is a cheaper alternative to multi-stream recycling. As far as can be ascertained, this is one of the few studies of its kind to examine the differences in material management costs and recycling performance between single and multi-stream recycling systems. This topic is of increasing importance, as single stream recycling is being touted as preferred waste management option in both Ontario and abroad.